2021
DOI: 10.21037/atm-20-1745
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of intense pulsed light with optimal pulse technology on meibomian gland dysfunction with and without ocular Demodex infestation

Abstract: Background: To evaluate the therapeutic effect of intense pulsed light (IPL) therapy with optimal pulse technology (OPT) on meibomian gland dysfunction (MGD) with and without ocular Demodex infestation. Methods: This prospective study included 150 patients with MGD who were divided into Demodex-infested (DI) and non-infested (control) groups according to Demodex counts determined by epilating eyelashes to evaluate. Each patient underwent three OPT treatment sessions at 3-week intervals. Best corrected visual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
2
13
0
1
Order By: Relevance
“…Some of the measured parameters have improved through follow-up in both study groups, but the IPL-MGX groups showed greater improvement than the control group in the OSDI score, NBUT (weeks 12 and 15), CFS (weeks 12 and 15), eyelid margin abnormalities, MGX (weeks 9 and 12), and meibum quality. These findings were consistent with our earlier studies showing the effectiveness of IPL as a treatment for MGD and ocular demodicosis [ 14 , 22 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Some of the measured parameters have improved through follow-up in both study groups, but the IPL-MGX groups showed greater improvement than the control group in the OSDI score, NBUT (weeks 12 and 15), CFS (weeks 12 and 15), eyelid margin abnormalities, MGX (weeks 9 and 12), and meibum quality. These findings were consistent with our earlier studies showing the effectiveness of IPL as a treatment for MGD and ocular demodicosis [ 14 , 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…The Snellen BCVA score was included for safety assessment when we designed this experiment. Unexpectedly, the vision of participants treated with IPL-MGX showed a remarkable improvement that persisted through all three follow-up assessments (all p < 0.001), unlike the patients with non-SS DE in our previous IPL experiment [ 14 ]. Although the differences between the treatment and control groups did not reach the significance level, we were satisfied with the significant improvement in visual acuity in some patients, including those in which topical cyclosporine or autologous serum treatment had failed.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…When Demodex mites infect the margin of the eyelid, the skin of the margin of the eyelid, the hair follicles and glands of the eyelid, and the meibomian glands will accumulate mites, and symptoms related to dry eye will occur ( 138 ). In addition, a typical clinical manifestation of Demodex blepharitis is cylindrical dandruff at the root of the eyelash, and this is considered pathognomonic for Demodex blepharitis ( 139 ). To detect Demodex mites, an optical microscope is used to examine eyelashes with typical cylindrical dandruff characteristics.…”
Section: Tear Examinationmentioning
confidence: 99%